Gaza War : new Palestinian resolve change paradigm - James M. Dorsey (2014)
The latest Israeli-Palestinian conflagration in Gaza constitutes a watershed with Israel struggling to counter mounting international criticism of its disproportinate use of force and Palestinians' increasingly united refusal of agreements that do not take into account their interests. A new paradigm could emerge involving Palestinian civil disobedience to force Israel to seriously negotiate an end to the Israeli-Palestinian conflict.